2019
DOI: 10.1002/cam4.2181
|View full text |Cite
|
Sign up to set email alerts
|

Durable response for ampullary and duodenal adenocarcinoma with a nab‐paclitaxel plus gemcitabine ± cisplatin combination

Abstract: Background/Aim There is no standard salvage chemotherapy for metastatic periampullary adenocarcinoma and duodenal adenocarcinoma and the prognosis of those who fail oxaliplatin, irinotecan, and 5FU is dismal. We examined nanoparticle albumin‐bound paclitaxel (nab‐paclitaxel) as salvage therapy for these two malignancies. Methods Patients who failed oxaliplatin, irinotecan, and 5FU and whose archival tumors stained immunohistochemical (IHC) tumor positive for CK7 or MUC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…This finding, which has been identified in a few small reports, supports the inclusion of taxane-based chemotherapy as an option beyond the first line in the NCCN guidelines. 8 , 25 , 26 , 27 Though used in a limited number of patients, neither TAS-102 nor regorafenib appeared to demonstrate meaningful activity with best response of PD seen in four of the five patients.…”
Section: Discussionmentioning
confidence: 89%
“…This finding, which has been identified in a few small reports, supports the inclusion of taxane-based chemotherapy as an option beyond the first line in the NCCN guidelines. 8 , 25 , 26 , 27 Though used in a limited number of patients, neither TAS-102 nor regorafenib appeared to demonstrate meaningful activity with best response of PD seen in four of the five patients.…”
Section: Discussionmentioning
confidence: 89%
“…Looking at the cellular contents of lesions, both ampullary and duodenal adenocarcinomas have been treated in a similar way; the treatment regimens were close to cholangiocarcinoma or colon cancer. Pharmacological regimens included gemcitabine w/wo platinum compounds (cis-or oxali-) [62] or Capacitabine and Oxaliplatinum [63,64]. Another pharmacological treatment involved the fluoropyrimidine-based chemotherapy (FOLFOX or FOLFIRI).…”
Section: Ihc and Its Predictive Role In Aacsmentioning
confidence: 99%
“…Furthermore, some authors in 2019 changed the third line of chemotherapy in three AAC patients, looking for their immunophenotypical characterizations. A group of scientists performed analyses of CK7, CK20, MUC1, and CDX2 in tumour tissues of patients [62]. The IHC analyses were suggestive for the PB subtype for two patients and the INT subtype for the third one.…”
Section: Ihc and Its Predictive Role In Aacsmentioning
confidence: 99%
“…Several RCT studies have shown that postoperative adjuvant chemotherapy for periampullary carcinoma does not improve patient survival [11][12][13][14]. Notably, most of the currently recommended chemotherapy regimens for AC were extrapolated from limited phase II clinical trials [15].…”
Section: Develop the Predictive Nomogrammentioning
confidence: 99%